THE EFFECT OF GIVING LAMTORO LEAF (Leucaena leucocephala) JUICE THROUGH DRINKING WATER ON ABDOMEN FAT DISTRIBUTION OF MALE BALI DUCKS - I D. G. S., Putra; Wibawa, A. A. P. P.; Siti, N. W. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This research aims to determine the effect of giving lamtoro leaf juice (Leucaena leucocephala) through drinking water on the distribution of abdominal fat in male Bali ducks. This research was conducted for 8 weeks at Sesetan Farm, Faculty of Animal Husbandry, Udayana University, Bali. The experimental design used was a completely randomized design (CRD) with four treatments and four replications. The four treatments were the level of lamtoro 126 leaf juice through drinking water, namely: 0%, 2%, 4%, and 6% as treatments P0, P1, P2, and P3. Each replicate consisted of 3 ducks, male Bali ducks used was 48 with a weight of 45.29 ± 2.8 g. Rations and drinking water were provided ad libitum. The variables observed were the percentage of pad fat, the percentage of mesenteric fat, the percentage of ventricular fat, and the percentage of abdominal fat. The results showed that administration of 6% (P3) of lamtoro leaf juice significantly (P<0.05) reduced the percentage of bearing fat and abdominal fat. Administration of 4% (P2) and 6% (P3) significantly (P<0.05) reduced the percentage of ventricular fat compared to the control treatment. Administration of 2-6% did not significantly (P>0.05) reduce the percentage of mesenteric fat. Based on the results of the study it can be concluded that administration of 6% lamtoro leaf juice can reduce the percentage of bearing fat, ventricular fat, and abdominal fat, while 4% administration of lamtoro leaf juice can reduce the percentage of ventricular fat. However, administration at a level of 2-6% has not been able to reduce the percentage of mesentery fat in male Bali ducks.